2020
DOI: 10.1016/j.fertnstert.2020.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of G-TL and global media for blastocyst culture in the EmbryoScope: morphokinetics, pregnancy, and live births after single-embryo transfer

Abstract: Objective: To evaluate the efficacy of two different in vitro fertilization culture media for blastocyst development, pregnancy, and live birth rate. Global (GB) medium (used without refreshment) and G-TL medium (designed specifically for culture in time-lapse incubators) were compared. Design: Prospective randomized study of sibling embryo culture in two culture media. Setting: In vitro fertilization clinic. Patient(s): Women undergoing fresh or frozen cycles using autologous or donor oocytes. Intervention(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…More importantly, TLT can also be used to identify and monitor in vitro stress that may arise from suboptimal culture conditions. In particular, a large number of consumables or new culture media for testing could interfere with anticipated cleavage timings [ 13 , 14 ]. Although subtle changes may have no clinical consequences [ 14 , 15 ], larger deviations in morphokinetic behavior may reflect severe physiological problems [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, TLT can also be used to identify and monitor in vitro stress that may arise from suboptimal culture conditions. In particular, a large number of consumables or new culture media for testing could interfere with anticipated cleavage timings [ 13 , 14 ]. Although subtle changes may have no clinical consequences [ 14 , 15 ], larger deviations in morphokinetic behavior may reflect severe physiological problems [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One potential limitation in cycle 3 is the media refresh of G-TL performed at day 3, as this is not suggested by the manufacturer. Further improvement could be achievable via maximizing the full benefits of such single-step media without the need to refresh, as demonstrated previously [14].…”
Section: Discussionmentioning
confidence: 86%
“…The tPNf was shorter for embryos that developed into good-quality blastocysts in this study, in line with previously published data 2 6 26 27 28 . A few studies conducted with sizable datasets have confirmed that the choice of culture medium does not affect PN fading 29 30 31 . What is more, obtained results about the impact of tPNf on blastocyst quality were in line with previously published results 27 28 .…”
Section: Discussionmentioning
confidence: 99%